Model Epistemologi Pesantren Dalam Pembentukan Karakter Dan Etika Keilmuan Santri - Andrean, Fanny; Husni, Muhammad (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2026)
This study examines the epistemological model of Islamic boarding schools and its contribution to shaping students’ character and scholarly ethics through a literature-based approach. The analysis draws on academic works, classical texts, and previous studies to identify the epistemological patterns grounded in the integration of bayani, burhani, and irfani traditions. Findings indicate that the pesantren epistemology provides a foundation for character formation through exemplary conduct, discipline, and the habituation of moral values. Additionally, students’ scholarly ethics are developed through the sanad system, respect for teachers, and the ethical principles of learning embedded in pesantren traditions. The study concludes that this epistemological model plays a strategic role in maintaining academic integrity and fostering students’ moral and intellectual responsibility.